2021
DOI: 10.1096/fj.202100731r
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal calcium sensor 1 (NCS1) dependent modulation of neuronal morphology and development

Abstract: Calcium (Ca 2+ ) signaling is critical for neuronal functioning and requires the concerted interplay of numerous Ca 2+ -binding proteins, including neuronal calcium sensor 1 (NCS1). Although an important role of NCS1 in neuronal processes and in neurodevelopmental and neurodegenerative diseases has been established, the underlying mechanisms remain enigmatic. Here, we systematically investigated the functions of NCS1 in the brain. Using Golgi-Cox staining, we observed a reduction in dendritic complexity and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
(197 reference statements)
1
5
0
1
Order By: Relevance
“…This study is the first report showing a decrease in NCS1 after taxane exposure in humans. The decrease in NCS1 levels over the course of taxane treatment in patients (Fig 4A ) follows the findings in pre-clinical models [14][15][16][17][18]. From these studies, alterations in intracellular calcium signaling is a likely critical pathway leading to calcium-related dysfunction occurring during chemotherapy.…”
Section: Plos Onesupporting
confidence: 78%
See 2 more Smart Citations
“…This study is the first report showing a decrease in NCS1 after taxane exposure in humans. The decrease in NCS1 levels over the course of taxane treatment in patients (Fig 4A ) follows the findings in pre-clinical models [14][15][16][17][18]. From these studies, alterations in intracellular calcium signaling is a likely critical pathway leading to calcium-related dysfunction occurring during chemotherapy.…”
Section: Plos Onesupporting
confidence: 78%
“…NCS1 is a high affinity, low-capacity calcium binding protein which modulates calcium signaling inside cells. NCS1 is particularly important for key functions in neurons such as dendritic arborization [18]. Previous studies have shown that exposure to taxanes triggers proteolysis of NCS1 by calpain [13,14], a ubiquitous enzyme that is activated when calcium levels are increased.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…NCS1 is a calcium sensor expressed predominantly in neurons that regulates many cellular functions, including neurotransmission, synaptic plasticity, exocytosis and endocytosis, neuronal growth, neuroprotection, and nuclear Ca 2+ regulation. Interestingly, NCS1 exerts similar functions as WFS1: both proteins regulate cytosolic Ca 2+ levels and IP3R-dependent ER-Ca 2+ release 20 , 32 , 33 , 34 modulate neuronal morphology and neurodevelopment, 49 , 50 mediate neuroprotection, 51 and have been implicated in neurodegenerative diseases and psychiatric disorders beyond WS. 52 , 53 , 54 In human fibroblasts, NCS1 knockdown impaired Ca 2+ homeostasis and mitochondrial function, demonstrating that NCS1 modulated [Ca 2+ ] m uptake and could be a target to maintain mitochondrial function and MAM integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Nesprin-1 (Syne 1) has been shown to play critical roles in neurogenesis and neuronal migration in mice [ 32 ]. Neuronal calcium sensor 1 (Ncs1) was reported to modulate neuronal morphology and development [ 33 ]. Glycogen synthase kinase-3 beta (Gsk3b) inhibition activates neurogenesis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%